2013
DOI: 10.1002/pola.26927
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of unsymmetrical benzonitrile‐containing polyimides: Viscosity‐lowering effect and dielectric properties

Abstract: A new unsymmetrical diamine, 2-(3-aminophenoxy)-6-(4-aminophenoxy)benzonitrile (3,4-APBN), is synthesized via two consecutive S N Ar reactions and the temperature-dependent reactivity of the fluorides in 2,6-difluorobenzonitrile, whose first S N Ar reaction occurs at 70 C and second, at 100 C, allowing timing control of reaction sequence and circumventing the transetherification side reaction. Thus, a series of polyimides (PIs) is prepared from the polymerization of 3,4-APBN with five common dianhydrides (6FDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…[35][36][37] An example of PI synthesis is described in Section I of the ESI. [35][36][37] An example of PI synthesis is described in Section I of the ESI.…”
Section: Pi Synthesis and Lm Preparation For Dielectric Characterizamentioning
confidence: 99%
“…[35][36][37] An example of PI synthesis is described in Section I of the ESI. [35][36][37] An example of PI synthesis is described in Section I of the ESI.…”
Section: Pi Synthesis and Lm Preparation For Dielectric Characterizamentioning
confidence: 99%
“…In our previous work, an asymmetric and two symmetric diamino monomers as well as the resulting PIs containing a single nitrile group per repeat unit were synthesized. We found that the enhanced entropy resulted from the presence of asymmetric structure in each repeat unit improved the processing of poly(amic acids) into PI films with increased dielectric constants and relatively low dielectric loss . As a continuing effort to probe additional structural factors, for example, dipole moment density to balance the need for high dielectric constant, low dielectric loss, and thermal stability as well as processability in developing high temperature capacitors, we report here the synthesis of new PIs containing three nitrile groups in each repeat‐unit structure, their thermochemical stability and film fabrication as well as thermal, mechanical, and dielectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the reactivity of benzonitriles was far lower than that of phthalonitriles, and azeotropic operations (temperatures around 140–180 °C) were essential for the complete substitution . Furthermore, obvious trans‐etherification (up to 10 −2 –10 −1 scale) would occur during the substitution of the second fluorine, especially when the second phenol has similar or higher reactivity ,. By using CaO@AC as the catalyst, reaction temperature can be significantly lowered; and asymmetric products could be obtained in excellent purity and yields.…”
Section: Resultsmentioning
confidence: 99%